Minor platforms in videogame history - Nicoll, Benjamin (Lecturer in digital media) (Games and play., 2019)
Videogame history is not just a history of one successful technology replacing the next. It is also a history of platforms and communities that never quite made it; that struggled to make their voices heard; that aggravated against the conventions of the day; and that never enjoyed the commercial success or recognition of their major counterparts. In Minor Platforms in Videogame History, Benjamin Nicoll argues that 'minor' game histories are anything but insignificant. Through an analysis of transitional, decolonial, imaginary, residual, and minor videogame platforms, Nicoll seeks out moments of difference and discontinuity in game history. From the domestication of vector graphics in the early years of videogame consoles to the proliferation of videogame piracy in South Korea in the 1980s, this book explores case studies that challenge taken-for-granted approaches to videogames, platforms, and their histories.